2006
DOI: 10.1111/j.1439-0426.2007.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on evolutionary mechanisms of osmotic and ionic regulation in Acipenseridae: an overview

Abstract: The changes in osmolarity and ion concentrations of blood serum, urine and intestinal liquid in different acipenserid species were studied during their acclimation to sea water, identifying the osmotic and ionic regulation involved in these species. The freshwater species (Acipenser ruthenus, A. baerii from Baikal Lake) can adapt to brackish water of 12.5‰ salinity as a conformer. The freshwater species Pseudoscaphyrhinchus kaufmanni is also an osmo-conformer, but tolerates brackish water up to 10‰ salinity on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
2
9
0
2
Order By: Relevance
“…The freshwater osmolality and ion levels found in this study were similar to those found in other acipenserids (McEnroe & Cech, 1985;Altinok et al, 1998;LeBreton & Beamish, 1998;McKenzie et al, 1999;Martinez-Alvarez et al, 2002;Rodriguez et al, 2002;Baker et al, 2008;Amiri et al, 2009;He et al, 2009;Zhao et al, 2011) including studies on A. brevirostrum (Jarvis & Ballantyne, 2003;Krayushkina, 2006). As noted in previous studies, the resting freshwater osmolyte concentrations of acipenserids are generally lower than those found in most teleosts (Kieffer et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…The freshwater osmolality and ion levels found in this study were similar to those found in other acipenserids (McEnroe & Cech, 1985;Altinok et al, 1998;LeBreton & Beamish, 1998;McKenzie et al, 1999;Martinez-Alvarez et al, 2002;Rodriguez et al, 2002;Baker et al, 2008;Amiri et al, 2009;He et al, 2009;Zhao et al, 2011) including studies on A. brevirostrum (Jarvis & Ballantyne, 2003;Krayushkina, 2006). As noted in previous studies, the resting freshwater osmolyte concentrations of acipenserids are generally lower than those found in most teleosts (Kieffer et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…Rochard et al, (1990) identified three types of life history style in sturgeons and according to them the Persian sturgeon belongs to type 2. Similarly, the acclimation capacity of Persian sturgeon to various salinities fits also the scheme suggested by Krayushkina (2006). Spending most of its life in the Caspian Sea with salinities ranging between 10 to 15 ppt.…”
Section: Blood Serum Osmolarity and Ion Concentrations (Na + K + supporting
confidence: 81%
“…Osmoregulation has extensively been studied in various acipenserids around the world, including the Caspian Sea (Krayushkina, 1963(Krayushkina, , 1967(Krayushkina, , 1983(Krayushkina, , 2006Magnin, 1963;Potts and Rudy, 1972;Moiseenko, 1977a, 1977b;Methalov, 1977;Wallace et al, 1993;McEnroe and Cech, 1985;Cataldi et al, 1995Cataldi et al, , 1999Krayushkina et al, 1996aKrayushkina et al, ,1996bKazemi et al , 2001Kazemi et al , , 2002Kazemi et al , and 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The sterlet is freshwater species which very rarely ascends the brackish water of rivers (Krayushina, 2006). …”
Section: Introductionmentioning
confidence: 99%